2016
DOI: 10.4238/gmr.15028014
|View full text |Cite
|
Sign up to set email alerts
|

Association of NT-proBNP and interleukin-17 levels with heart failure in elderly patients

Abstract: ABSTRACT. Pro-B-type natriuretic peptide (NT-proBNP) and interleukin-17 (IL-17) are involved in the pathophysiological processes of heart failure; however, the exact role of IL-17 is not clear. We explored the relationship between IL-17 and NT-proBNP, as a clinical parameter, in heart failure. The whole blood IL-17 and NT-proBNP levels and the readmission rates in 70 patients with chronic heart failure class III or IV according to the New York Heart Association and 35 patients with normal heart function (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…IL‐17A is produced by activated T cells, has been shown to regulate myocardial fibrosis in experimental models of HF through a RANKL‐dependent mechanism . In our study, we observed an upregulated level of IL‐17A in patients and is in line with earlier findings showing a higher IL‐17A mRNA expression in congestive HF . In addition, we noticed lower level of TGF‐β in patients with HF as compared to healthy controls matched with earlier reports suggesting a decrease in circulating levels of TGF‐β1 during heart failure and it correlates with increased markers of inflammation …”
Section: Discussionsupporting
confidence: 92%
“…IL‐17A is produced by activated T cells, has been shown to regulate myocardial fibrosis in experimental models of HF through a RANKL‐dependent mechanism . In our study, we observed an upregulated level of IL‐17A in patients and is in line with earlier findings showing a higher IL‐17A mRNA expression in congestive HF . In addition, we noticed lower level of TGF‐β in patients with HF as compared to healthy controls matched with earlier reports suggesting a decrease in circulating levels of TGF‐β1 during heart failure and it correlates with increased markers of inflammation …”
Section: Discussionsupporting
confidence: 92%
“…Similar to in humans, our data suggest that the levels of ANP and BNP may both be important leading indicators of cardiac disease in nonhuman primates. In humans, the level of NT-proBNP, a hormone that is produced by the decomposition of the BNP precursor proBNP, is also an important cardio-specific marker for heart failure [ 6 , 17 , 28 ]. However, NT-proBNP has specificities not only between animal species, but also between human races [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 induces myocardial fibrosis and decreases collagen synthesis. Elevated levels of IL-17 have been shown to be associated with advanced New York Heart Association (NYHA) classes of HF, III, and IV [19]. However, the role of IL-17 in HF progression is unclear.…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 98%